Оценка степени кристалличности природного и синтетического диоксида кремния; Известия вузов. Физика; Т. 66, № 4 - Коровкин М. В. Михаил Владимирович; Ананьева Л. Г. Людмила Геннадьевна; Жерлицын А. А. Алексей Алексеевич; Кондратьев С. С. Сергей Сергеевич; Савинова О. В. Олеся Вячеславовна; Курская В. С. Виктория Сергеевна (2023, 2023)
Заглавие с экрана